Promoting Intra-Firm Transfer Of Knowledge Through Competition - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
This paper examines three main COliCell1S about intro-firm transfer on knowledge in the management accounting and strategic. nicmcigemen I literature: the ability of real-world organizations to learn productively, the levels of aggregation in which the productive learning occurs, and the types of. maim gement interventions that are both desirable and pmcluctive. Based on a field study conducted in several business units of a multinational corporation, this paper reports how management makes conscious and systematic efforts to transform ideas from the best practice within the company cis well as front its competitors. The company uses Management By Olympic Systems to accelerate learning through competition and sharing. The system utilizes Olympic principles and integrates individual mid team concepts to achieve the Olympic targets. A broad range ofOl yin pic targets in terms of financial cmd non-financial linked to the company's incentive systems is used to improve business operations, to motivate managers and employees, and to meet stakeholders' expectations.